Freedom and shared storytelling in J R R Tolkien's "The Lord of the Rings" - Bird, Tanya (University of Ottawa (Canada), 2003)
This thesis explores the freedom of shared storytelling in Tolkien's seminal essay, "On Fairy-Stories," and applies these principles to his fiction. In The Lord of The Rings, authentic storytelling is developed not through domination of others, but within the context of free relationships. Ultimately, the literary freedom that the author enjoys, and extends to the audience or to characters, is grounded in the Primary Creator's gift of freedom and invitation to engage in "subcreation." While Sauron ruptures the subcreative relationship by forging the ring of power to dominate others ("magic"), the elves, hobbits and other creatures share narrative ("enchantment"), affirming being through "recovery." Recovery counteracts Sauron's determinism and enables hope for "eucatastrophe," the redemptive grace at the heart of stories. Tolkien offers a unique alternative to secular models of literary freedom: human agency may be represented in literature not only through independence from divine intervention, but also in collaboration with it.
Keywords: Literature, Modern.; Literature, English.